Isolation of Bacillus paralichenifromis BL-1 and Its Potential Application in Producing Bioflocculants Using Phenol Saline Wastewater - Tao Zhang; Rongkai Guo; Fanshu Liu; Lei Zhang; Linxiao Li; Rongfei Zhang; Chaogang Shao; Junbo Zhou; Fan Ding; Lan Yu (Microbiology Research)
Phenolic compounds are harmful organic pollutants found in wastewater from the chemical and pharmaceutical industries, which are frequently accompanied by high saline concentrations. Microorganism-based biodegradation represents an environmentally friendly and cost-effective strategy for phenol removal. In this study, we isolated a bioflocculant-producing Bacillus paralicheniformis BL-1 that is capable of phenol degradation in high-salinity conditions. Differential gene expression analysis revealed the down-regulation of genes related to the synthesis of extracellular polymeric substances and the up-regulation of poly-γ-glutamate biosynthesis in 10% NaCl conditions. These findings indicate that poly-γ-glutamate is the main large biomolecule produced by B. paralicheniformis BL-1. A further investigation suggested that salinity stress resulted in the down-regulated expression of the genes involved in iron homeostasis. Therefore, alleviating iron limitation by supplying excess iron could improve cell growth and, thus, increase the phenol removal rate and flocculating activity. The productivity of poly-γ-glutamate reached 2.23 g/L, and the phenol removal rate reached 73.83% in the synthetic medium supplemented with 10% NaCl, 500 mg/L phenol, and 250 μM FeCl3.